Concentrations of blood styrene and neurobehavioral function among Gulf state residents in the U.S. - Choi, Giehae; Rohlman, Diane S.; Kwok, Richard K.; Werder, Emily J.; Lawrence, Kaitlyn G.; Blair, Aaron; Miller, Aubrey K.; Jackson II, W. Braxton; Sandler, Dale P.; Engel, Lawrence S. (International Journal of Environmental Health Research, 2025)
Objectives: To investigate relationships between blood styrene concentrations and neurobehavioral function among US Gulf State residents. Methods: Our study includes 328 Gulf state residents enrolled in the Gulf Long-term Follow-up Study with data on blood styrene concentrations (2012–2013) and neurobehavioral test results (2014–2016, Behavioral Assessment and Research System and trail making test). We estimated the differences in test scores by blood styrene quartiles and explored effect measure modification by smoking. Results: Styrene was detected in 77% of participants (median: 0.06 ng/ml). We observed only weak associations and no apparent dose–response relationships between styrene levels and performance on any neurobehavioral tests, although some associations were more prominent in males. For some neurobehavioral tests, we observed modestly stronger associations among participants with higher cotinine levels (>15 ng/mL). Conclusion: We found limited support for an association between low-level blood styrene concentration and neurobehavioral test performance, although some associations were stronger among smokers.